2017
DOI: 10.1007/s11930-017-0137-y
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Erectile Dysfunction and Subclinical Cardiovascular Disease

Abstract: Purpose of review We review the recent literature on the hypothesized temporal relationship between subclinical cardiovascular disease (CVD), vascular erectile dysfunction (ED), and clinical CVD. In addition, we combine emerging research with expert consensus guidelines such as The Princeton Consensus III to provide a preventive cardiologist’s perspective toward an ideal approach to evaluating and managing CVD and ED risk in patients. Recent findings Development of ED was found to occur during the progressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…337À341 There is strong evidence that CVD risk assessment is needed in men presenting with ED. 336,342 In men with ED and low-to-intermediate CVD risk, detailed risk profiling by, for example, CAC score is suggested, but so far not supported by evidence. 338,341 Assessment of ED severity and physical examination should be part of the first-line CVD risk assessment in men.…”
Section: Non-alcoholic Fatty Liver Diseasementioning
confidence: 99%
“…337À341 There is strong evidence that CVD risk assessment is needed in men presenting with ED. 336,342 In men with ED and low-to-intermediate CVD risk, detailed risk profiling by, for example, CAC score is suggested, but so far not supported by evidence. 338,341 Assessment of ED severity and physical examination should be part of the first-line CVD risk assessment in men.…”
Section: Non-alcoholic Fatty Liver Diseasementioning
confidence: 99%
“…The association between HCV and atherosclerosis is an emerging topic (Goossens & Negro, 2017; Ishizaka, Ishizaka, & Yamkado, 2014; Katsi et al., 2015). Atherosclerosis is an important contributor for sexual dysfunction (Gowani et al., 2017; Miner et al., 2019). The DAA therapy had advantage of improvement of atherosclerosis (Butt et al., 2019; Ichikawa et al, 2019) and therefore is beneficial in sexual function in patients with HCV.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the theory that progressive occlusive atherosclerotic disease may manifest earlier in smaller penile arteries than in larger coronary arteries [ 9 ], numerous studies have demonstrated the predictive ability of ED for future CVD events [ 10 11 ]. The ED symptoms precede clinically overt CVD by 2–3 years [ 12 13 ], and more severe ED is associated with an increased risk of CVD [ 14 15 ]. However, it remains unclear whether severe ED can predict future CVD events in men undergoing dialysis, who are generally recognized as at high-risk for accelerated atherosclerosis [ 16 ].…”
Section: Introductionmentioning
confidence: 99%